2012
DOI: 10.1186/1743-422x-9-128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating viral interference between Influenza virus and Newcastle disease virus using real-time reverse transcription–polymerase chain reaction in chicken eggs

Abstract: BackgroundSimultaneous and sequential allantoic cavity inoculations of Specific-pathogen-free (SPF) chicken eggs with Influenza virus (AIV) and Newcastle disease virus (NDV) demonstrated that the interaction of AIV and NDV during co-infection was variable. Our research revisited the replication interference potential of AIV and NDV using real-time reverse transcription–polymerase chain reaction (real-time RT-PCR) for AIV and NDV to specifically detect the viral genomes in mixed infections.ResultsData from this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 36 publications
2
40
3
Order By: Relevance
“…Co-infections of AIV and NDV have been studied in vitro using cell cultures or chicken embryos, and interference between these viruses has been reported, with one virus inhibiting the growth of the other [7,28-32]. …”
Section: Discussionmentioning
confidence: 99%
“…Co-infections of AIV and NDV have been studied in vitro using cell cultures or chicken embryos, and interference between these viruses has been reported, with one virus inhibiting the growth of the other [7,28-32]. …”
Section: Discussionmentioning
confidence: 99%
“…IAV and APMV-1 utilize the a 2,3 sialic acid receptors on host cells, and may compete for host cell machinery during viral replication (Markwell, 1991). In lab studies, it has been demonstrated that there are limited synergistic or competition effects between IAV and APMV-1, but thus far studies have failed to provide a conclusive picture of the interactions at the host level (Franca et al, 2014;Ge et al, 2012;Tolf et al, 2013b). Regardless 1 1 2 1 1 1 1 1 2 1 1 2 2 1 1 1 1 1 1 1 2 3 3 1 4 1 2 3 2 2 1 2 2 3 5 1 2 4 1 2 1 1 1 2 1 2 2 1 1 1 2 1 1 2 3 4 2 1 2 2 5 6 2 1 Solid lines depict the mean prediction and dotted lines the 95% confidence interval of the predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these viruses co-circulate in poultry in many parts of the world and domestic ducks are considered reservoirs and source of these viruses for other poultry species, NDV and AIV co-infections in domestic ducks are not well understood. AIV and NDV co-infections have been studied in vitro using cell cultures or chicken embryos, and interference between these viruses has been demonstrated, with one virus inhibiting the growth of the other (Bang, 1949; Carr, 1960; Ge et al, 2012; Shortridge and King, 1983). Contrary to in vitro or in ovo settings, in vivo experiments examine the overall effect of co-infections by incorporating the complexity of the whole organism, including target cells and immune responses (Costa-Hurtado et al, 2014).…”
Section: Discussionmentioning
confidence: 99%